2018
DOI: 10.1111/lang.12300
|View full text |Cite
|
Sign up to set email alerts
|

An Open for Replication Study: The Role of Feedback Timing in Synchronous Computer‐Mediated Communication

Abstract: This study investigated the role of corrective feedback timing in the acquisition of Spanish noun–adjective gender agreement. Forty‐five learners completed a communicative task via synchronous computer‐mediated communication (SCMC) in one of three groups (immediate, delayed, control). The immediate‐feedback group received error reformulations immediately after their errors. The delayed‐feedback group did not receive feedback; however, at the end of the task, they were provided with an electronic document showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 53 publications
(87 reference statements)
1
45
2
Order By: Relevance
“…Exploring the effectiveness and ineffectiveness of immediate‐feedback and delayed feedback, Arroyo and Yilmaz (2018) confirmed the affordance of developing oral production via immediate‐feedback. The study also referred to the issue of difficulty to draw conclusions concerning the impact of feedback timing and suggested the use of same procedures and materials across studies.…”
Section: Resultsmentioning
confidence: 96%
“…Exploring the effectiveness and ineffectiveness of immediate‐feedback and delayed feedback, Arroyo and Yilmaz (2018) confirmed the affordance of developing oral production via immediate‐feedback. The study also referred to the issue of difficulty to draw conclusions concerning the impact of feedback timing and suggested the use of same procedures and materials across studies.…”
Section: Resultsmentioning
confidence: 96%
“…Three other studies, Li, Zhu, and Ellis (2016b) and Arroyo and Yilmaz (2017, 2018) have found an advantage for immediate CF over delayed. In a face-to-face classroom study, Li et al (2016b) examined corrective recasts provided on past passive errors either immediately after the error or delayed until the end of two consecutive dictogloss tasks.…”
Section: Introductionmentioning
confidence: 89%
“…in a later turn in the discourse, at the end of a task or a lesson, or days later) occurs naturally in L2 classrooms (Fu & Nassaji, 2016; Hunter, 2012; Loewen, 2004; Rolin-Ianziti, 2010) and is recommended in teacher training materials during fluency-focused activities to minimize disrupting communicative activities (Harmer, 2007; Hedge, 2000; Scrivener, 2005). Delayed CF may also be an attractive alternative to immediate CF in online instructional contexts where providing immediate CF may not always be feasible (Arroyo and Yilmaz, 2017, 2018). CF timing research also has implications for some of the mainstream SLA theories underscoring the importance of providing CF immediately (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, one topic that has received little attention in the research but is of theoretical and pedagogical significance is the timing of CF, that is, whether CF should be provided immediately after an error is made during a communicative task or whether it should be postponed until the task is completed. In this article, I call for the replication of two recently published studies on the comparative effectiveness of immediate and delayed feedback: Li et al (2016) and Arroyo & Yilmaz (2018).…”
Section: Introductionmentioning
confidence: 98%
“…The treatments of the studies were theoretically justified and consistently implemented, and the treatment effects were assessed via valid measures. Of course, the rigor of the studies is also buttressed by the fact that they were published in prestigious journals in the field: Modern Language Journal (Li et al 2016) and Language Learning (Arroyo & Yilmaz 2018). Fifth, both studies provided detailed information about their procedures and made their materials and instruments available on IRIS (Marsden, Plonsky & Mackey 2016)—a free, open depository of research materials in applied linguistics—or as supplementary information at the journal website.…”
Section: Introductionmentioning
confidence: 99%